2002
DOI: 10.1152/ajprenal.00023.2002
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase G activates inwardly rectifying K+channel in cultured human proximal tubule cells

Abstract: An ATP-regulated inwardly rectifying K(+) channel, whose activity is enhanced by PKA, is present in the plasma membrane of cultured human proximal tubule cells. In this study, we investigated the effects of PKG on this K(+) channel, using the patch-clamp technique. In cell-attached patches, bath application of a membrane-permeant cGMP analog, 8-bromoguanosine 3',5'-monophosphate (8-BrcGMP; 100 microM), stimulated channel activity, whereas application of a PKG-specific inhibitor, KT-5823 (1 microM), reduced the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 37 publications
(57 reference statements)
3
17
1
Order By: Relevance
“…4C). This is in good agreement with the previous observation that 8-BrcGMP restored the suppressed channel activity by KT-5720 (28). Summarized data are shown in Fig.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…4C). This is in good agreement with the previous observation that 8-BrcGMP restored the suppressed channel activity by KT-5720 (28). Summarized data are shown in Fig.…”
Section: Resultssupporting
confidence: 92%
“…The inward slope conductance, which was measured between Ϫ90 and Ϫ30 mV of ϪV p , was 42.8 Ϯ 1.1 pS, whereas the outward slope conductance between ϩ30 and ϩ90 mV was 8.5 Ϯ 2.7 pS. These measurements almost fit with the previous results obtained from inside-out patches under the symmetrical high-K ϩ condition (28,29). When the bath was replaced with the control solution, the current-voltage curve shifted to the right with the change in reversal potential from ϩ10 to ϩ75 mV (Fig.…”
Section: Methodssupporting
confidence: 89%
See 2 more Smart Citations
“…The activation of nNOS and eNOS, both of which require the elevation of [Ca] i , leads to the activation of a cGMP-mediated phosphorylation process [31]. Several reports have demonstrated that cGMP-mediated phsophorylation regulates inwardly rectifying K + channels in proximal tubule cells [6,32,33]. In the present study, however, the application of L-NNA or L-NAME to the bath did not affect the activity of inwardly rectifying K + channels ( Fig.…”
Section: Discussioncontrasting
confidence: 46%